Early settlement construction in Southeast Asia: lime mortar floor sequences at Loc Giang, southern Vietnam. (December 2022) - Grono, Elle; Piper, Philip J.; Kinh, Dang Ngoc; Bellwood, Peter; Denham, Tim; Friesem, David E.
Abstract: Abstract : Research on prehistoric mainland Southeast Asia is dominated by mortuary contexts, leaving processes such as the transition to sedentism relatively understudied. Recent excavations in southern Vietnam, however, have recovered new evidence for settlement. The authors report on investigations at the neolithic site of Loc Giang (3980–3270 cal BP) in southern Vietnam, where excavation revealed a vertical sequence of more than 30 surfaces. Microarchaeological analyses indicate that these features are carefully prepared lime mortar floors; the lime was probably produced from burnt shell. The floors date to between 3510 and 3150 cal BP, providing the earliest-known evidence for the use of lime mortar, and for durable settlement construction, in this region.